Bone Healing Following Different Types of Osteotomy: Scanning Electron Microscopy (SEM) and Three-Dimensional SEM Analyses. (21st December 2016) - Blaskovic, Marko; Gabrić, Dragana; Coleman, Nichola J.; Slipper, Ian J.; Mladenov, Mitko; Gjorgievska, Elizabeta
Abstract: The aim of the present study was to compare dynamics of the bone healing process after different types of osteotomies. In total, 24 Wistar rats were subjected to different types of osteotomy performed with standard steel bur, piezosurgery, contact, and non-contact Erbium:yttrium-aluminum-garnet (Er:YAG) laser ablation. The animals were randomly divided into four groups, to be euthanized immediately after the procedure, or at 1, 2, or 3 weeks after surgery. The obtained bone samples were analyzed by scanning electron microscopy (SEM). Immediately after surgery, there were significant differences in the appearance of the bone defects, with presence of bone fragments and debris after standard steel bur preparation, compared with the clean smooth walls and relatively sharp edges in all other groups. The initial bone formation in defects prepared by piezosurgery was observed to be the most rapid. After 3 weeks, all bone defects were completely restored; although, differences in the healing pattern were noted, with a modest initial delay in healing after laser preparation. The first stage of the bone healing process was delayed when contact and non-contact Er:YAG laser modes were used and accelerated by piezosurgery; however, the results after 3 weeks demonstrated similar restitution of defects in all tested groups.